How the Risk of Tin Whiskers Affects Design Decisions: Is the Aerospace and Defense Approach to Tin Whiskers the Right Approach - Michael Pecht; Michael Osterman; Edwin C. Tinsley; Chang Lu (IEEE Access, 2025)
Most of the electronics industry, including piece part (electronic component) suppliers, have been involved with developing and implementing lead (Pb)-free risk reduction methods since the introduction and enforcement of RoHS in 2006. The most widely used standard to assess the risk of tin whiskers has been JESD201 “Environmental Acceptance Requirements for Tin Whisker Susceptibility of Tin and Tin Alloy Surface Finishes”. The JESD201 standard requires that aged samples be put through thermal cycling, humidity, high temperature, and ambient testing. Another companion standard, JESD22-A121 “Test Method for Measuring Whisker Growth on Tin and Tin Alloy Surface Finishes” can be used to assess the results of the JESD201 tests. If assemblies and piece parts meet the requirements of JESD201, it is generally expected that their use of Pb-free solders, finishes and plating should not result in tin whiskers that can cause failures. This approach is currently used in the commercial industry with products having lifetimes of up to 7 years, as well as in the automotive and gas industry with much longer expected lifetimes. This paper investigates the benefits of using this approach by industries, including the medical devices, aerospace and defense industries, that are still producing lead-based electronics.